2009
DOI: 10.5194/acp-9-6017-2009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prescribed SSTs on climatologies and long-term trends in CCM simulations

Abstract: Abstract. Chemistry-Climate Model (CCM) simulations are commonly used to project the past and future development of the dynamics and chemistry of the stratosphere, and in particular the ozone layer. So far, CCMs are usually not interactively coupled to an ocean model, so that sea surface temperatures (SSTs) and sea ice coverage are prescribed in the simulations. While for future integrations SSTs have to be taken from precalculated climate model projections, for CCM experiments resembling the past either model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…This would suggest a sensitivity in some models to the SSTs, as well as the need for accurate prediction of the SSTs to simulate the recovery of ozone. See also Garny et al [2009] and Austin and Wilson [2010].…”
Section: Evolution Of the Ozone Holementioning
confidence: 99%
“…This would suggest a sensitivity in some models to the SSTs, as well as the need for accurate prediction of the SSTs to simulate the recovery of ozone. See also Garny et al [2009] and Austin and Wilson [2010].…”
Section: Evolution Of the Ozone Holementioning
confidence: 99%
“…The simulation is identical to the SCN-B2d simulation described in Garny et al (2009), and a brief description of the model and the simulation is given in Appendix A. The demonstration of the method is largely independent of the details of the model.…”
Section: Introductionmentioning
confidence: 99%
“…the solar cycle, the quasi-biennial oscillation and major volcanic eruptions in the past are considered. Details on the simulation can be found in Garny et al (2009).…”
Section: Appendix a The E39c-a Model And Simulation Descriptionmentioning
confidence: 99%
“…2). Taking stratospheric ozone as an example (Q1), Braesicke and Pyle (2004) and Garny et al (2009) showed that the representation of sea surface temperatures have an impact on tropospheric and stratospheric ozone in the order of 10 %. The uncertainties in the input data give a limit to which a model can be evaluated.…”
Section: The Model Input Datamentioning
confidence: 99%